Praktik Akuntansi Keuangan Usaha Perajin Batik Di Kecamatan Pelayangan, Kota Jambi - Mukhzarudfa, Mukhzarudfa; Kusumastuti, Ratih (Jurnal Karya Abdi Masyarakat, 2019)
The UMKM center of culture-based superior products of Jambi City is the center of Batik development and Sulaman Mas which is located in the area across Jambi City (Sekoja) which is spread until October 2018 in 2 subdistricts, namely Teluk Teluk and Pelayangan. With the number of business units as many as 75 UMKM. The purpose of this activity is to increase participants' knowledge about recording and presenting financial statements (Balance Sheet, Profit and Loss Statement), properly and correctly by using SIAPIK software. Grow and increase the trust of bank and non-bank financial institutions towards SMEs.Good financial management requires a form of copying by using an information system. An information system that can be used in making checks and advising on financial statements. The batik craftsmen who met in the Sanggar Batik Kajang Lako, none of which made the writing and preparation of financial statements using a representative information system. Compliance and compilation of financial statements are still made manually.